Bodies, gender, and digital affect in fitspiration media. Issue 5 (4th July 2021) - Toffoletti, Kim; Thorpe, Holly
ABSTRACT: This paper takes an affective approach to theorizing the production and circulation of fitspiration media within a women's Instagram fitness community. In the context of fitness culture trends towards digitally networked, interactive, and quantified experiences, our study contributes to debates about the impacts of fitspiration media on women by investigating the expressions, feelings, and connections that arise through the self-presentation and circulation of "fit" body images on social media. We analyze 155 Instagram posts containing the hashtags #BBG, #thekaylamovement, #kaylasarmy, and #bbggirls to map the ways in which feelings are communicated by followers of a popular global fitness community led by celebrity influencer Kayla Itsines. In so doing, we reveal the ways in which intensities of feeling experienced in, through and about the body (i.e., pride, vulnerability, shame) work affectively to connect and compel exercising women.